Efektifitas Terapi Akkupuntur Terhadap Keberhasilan Rehabiltasi Pasien Pasca Stroke: Literature Review - Koernia Nanda Pratama; Galih Noor Alivian (Journal of Bionursing, 2019)
Introduction. Stroke is a sortie that occurs in the brain that involves blood vessels in the brain (blockage or cracked) and finally manifests in a various of symptoms (starting from paralysis, interference of swallowing and speaking, etc.). This disease is differentiated into ischemic-infarct strokes and hemorrhagic strokes. In Indonesia, this disease has increased from 7% to 10.9%. It indicates that stroke is a disease that is quite dangerous and needs an appropriate handling or rehabilitation.Objective. This study aims to collect and analyze articles relating to the effectiveness of acupuncture therapy as a stroke management.Method. Search for journal articles is done electronically by using several databases, namely DOAJ, PubMed and Google Scholar with the keywords "Acupunture for post stroke" for international journals, whereas for national journals using the Google Scholar search engine with the keyword "Acupuncture therapy in post-stroke patients", the journal sought is an intervention journal with PICO frame work criteria (Patient, Intervention, Comparison, Outcome). From the results of the review there were 5 journals that were relevant to the topic. The journal consists of 3 international journals and 2 national journals, the next step is to review the five journals.Results. Acupuncture therapy is effective for improving post-stroke rehabilitation. This therapy is giving a puncture to Meridian Yang Ming to facilitate the flow of the Ci-Meridian. In this meridian there is a complicated connection system called acupoints (acupuncture points) that binds or relates to various functions of the body and organs. In stroke patients, due to some nerve pathways have been closed it is difficult to maintain the opened circulation. With stimulation of acupuncture at some acupuncture points, it opens the blood vessels and improves the blood flow. Based on the results obtained from the research, acupuncture is quite effective in handling the rehabilitation of stroke patients. In order to feel the results optimally, stroke patients are recommended not only to do the acupuncture therapy. But also the other therapeutic activities.Discussion. The results of this test provide a general picture in the intervention group, that acupuncture therapy interventions can open up blood vessels so that the various effects or complications of stroke disease can be decreased.Conclusion. Acupuncture thrapy is effective for the successful rehabilitation of post-stroke patients..